If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -5t + 8s + -5t = 0 Reorder the terms: 3s + 8s + -5t + -5t = 0 Combine like terms: 3s + 8s = 11s 11s + -5t + -5t = 0 Combine like terms: -5t + -5t = -10t 11s + -10t = 0 Solving 11s + -10t = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '10t' to each side of the equation. 11s + -10t + 10t = 0 + 10t Combine like terms: -10t + 10t = 0 11s + 0 = 0 + 10t 11s = 0 + 10t Remove the zero: 11s = 10t Divide each side by '11'. s = 0.9090909091t Simplifying s = 0.9090909091t
| (6w-7)/5=7 | | 12p+p=5-20 | | -8x+13=29 | | 7+5(8z+7)= | | -2d=-3d+6 | | 6w-7= | | x^2+24x=-135 | | 3(3x-4)-5x=12 | | 42+x-42=138 | | 13/52x4/52 | | -9-c-10=9+3c | | 2d+-5=17 | | 3(4x-5)-(6x+3)= | | 12x+25+3x+10=180 | | -12=5(-2) | | x+3-3=-x | | -9r-8=5r-8 | | 4y-4-2x=0 | | -3b-[-2]=4b-12 | | 10x-(4x-2)=38 | | 4f(1/4x) | | 9-4/3y=5 | | 64+12x=7x-4 | | 54.8-d/5 | | .90x+6.80=.65x+7.30 | | -1/2h=-75 | | 3.2(2.3-0.5)= | | 3x=-4y+43 | | c/4=11=-5 | | 3x=36-12y | | 2(2X+3)-2=20 | | b-1+4b=32 |